The right attitude to rain - McCall Smith, Alexander, 1948- (Abacus, 2007)
Nothing captures the charm of Edinburgh like the bestselling Isabel Dalhousie series of novels featuring the insatiably curious philosopher and woman detective. Whether investigating a case or a problem of philosophy, the indefatigable Isabel Dalhousie, one of fiction’s most richly developed amateur detectives, is always ready to pursue the answers to all of life’s questions, large and small.